2021
DOI: 10.1155/2021/6614838
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Regionalizing Care in the Developing World: Impact of Distance to Referral Center on Compliance to Biopsy Recommendations in a Brazilian Prostate Cancer Screening Cohort

Abstract: Given growing specialization in medical care, optimal care may require regionalization, which may create access barriers. We tested this within a large prostate cancer (PC) screening program in Brazil. In 2004–2007, Barretos Cancer Hospital prospectively screened men for PC throughout rural Brazil. Men with abnormal screen were referred for follow-up and possible biopsy. We tested the link between distance from screening site to Barretos Cancer Hospital and risk of noncompliance with showing up for biopsy, PC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
2
0
3
Order By: Relevance
“…El acceso físico a los servicios de salud ha sido medido como distancia física del paciente con CaP a los servicios (Freedland et al 2021), y como cobertura espacial de los servicios de salud (Rivera et al, 2021). En ambos estudios se comprobó su influencia en la letalidad y mortalidad.…”
Section: Discusión De Los Resultadosunclassified
See 2 more Smart Citations
“…El acceso físico a los servicios de salud ha sido medido como distancia física del paciente con CaP a los servicios (Freedland et al 2021), y como cobertura espacial de los servicios de salud (Rivera et al, 2021). En ambos estudios se comprobó su influencia en la letalidad y mortalidad.…”
Section: Discusión De Los Resultadosunclassified
“…En el Reino Unido se evidenció que la prolongación de la vida y la calidad con que viven los pacientes de cáncer se asocia con la oferta de servicios de atención primaria (Gao et al, 2020). El acceso a los centros de derivación de pacientes, que es, muchas veces, el primer contacto del paciente con el sistema de salud, resultan decisivos en el éxito del tratamiento a posteriori (Freedland et al, 2021).…”
Section: Discusión De Los Resultadosunclassified
See 1 more Smart Citation
“…2 Moreover, studies have shown that mortality rates from Pca have increased over time in all regions of Brazil. 3 A family history of Pca is linked to an increased risk of high-grade disease, particularly in black men, who are more likely to be diagnosed with a more aggressive form of the disease on biopsy than non-Black men. However, most population studies investigating the relationship between family history and Pca have primarily involved men from white populations, and it is uncertain if the results apply to the black population, as highlighted by Jenkins et al in 2021.…”
Section: Introductionmentioning
confidence: 99%
“…It is also among the top five causes of cancer‐related deaths in men globally in 2021 and remains the leading cause of death among men in 89 countries 2 . Moreover, studies have shown that mortality rates from Pca have increased over time in all regions of Brazil 3 …”
Section: Introductionmentioning
confidence: 99%